INCREASING THE CAPACITY AND COMPETITIVENESS OF MSMES THROUGH EMPOWERMENT SEMINAR IN MUARA DUA DISTRICT - Muhammad Multazam; Azhari; Ismed Wijaya; Zulfa Salma Fatin; Tasyaul Azkia (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This community service activity aims to improve the capacity of Micro, Small, and Medium Enterprises (MSMEs) through a training program focused on business management, product marketing strategies, and the use of digital technology. The program employed Participatory Action Research (PAR) as its method, emphasizing active participant participation through interactive workshops and direct mentoring. The program was implemented in July 2024 and involved 30 participants from various MSME sectors in the Muara Dua sub-district. The results demonstrated a significant increase in participants' understanding of business management, marketing strategy development, and increased confidence in adopting new technologies. Technology implementation was evident in the use of social media as a primary tool in MSME product marketing strategies. Furthermore, this activity also had a positive impact on increasing revenue and expanding market reach for entrepreneurs. Strengthening networks between MSMEs, local governments, and local communities contributes to the creation of a sustainable and competitive business ecosystem in the future.